AB1142 Reduction of absolute number of cd4+cd25+foxp3+ treg cells is associated with pathological features of patients with idiopathic inflammatory myopathy. (12th June 2018) - Zhao, H.; Wen, H.Y.; Li, X.F.; Liu, Y.
Abstract : Objectives: To explore the alterations and their significance of peripheral CD4 + CD25 + FOXP3 + regulatory T cells (Tregs) and Th17 cells in Idiopathic inflammatory myopathy. Methods: Clinical indicators of IIM cases (n=85) and healthy controls(n=60) were enrolled. The absolute number of peripheral Tregs and Th17 cells were analysed by flow cytometry. The clinical features were collected retrospectively. Since the data was disregarded from the normal distribution, the median four quantile method was used for statistical description. Two samples were compared with Mann-Whitney U test, and the correlation between variables was Spearman rank correlation analysis. Results: ( 1 The absolute number of Treg cells in the patients was significantly lower than that in the control group ( P <0.05); the ratio of Th17/Treg was also significantly higher than that in the control group ( P <0.05) ; (2) Peripheral Treg cells levels were negatively correlated with CRP (r=0.279, p<0.05, ) (3) According to the involvement of important organs was classified into two groups: organ group and non-organ group. The absolute number of Treg cell in organ group is fewer than that in non-organ group (p<0.05), and the ratio of Th17/Treg in organ group was significantly higher than that in non-organ group. 4 The peripheral Th17 cell absolute number in patients with skeletal muscle inflammatory oedema was significantly higher than that of non inflammatory oedema patients (p<0.05); 6 The levels of Th17, Tregs and ratio of Th17/Treg did not correlated with pathological features of inflammatory infiltration (p>0.05). Conclusions: The absolute number of peripheralTreg cells decreased significantly in IIM, and correlated with CRP. Patients with organ involvement had fewer Treg cells, and imbalance between Th17 and Treg. When muscle MRI appeared inflammatory oedema, it has a higher level of Th17 cells. Our results suggest that Treg cells plays an important role in the pathogenesis of IIM and increasing the number of Treg cells and maintaining Th17/Treg immune balance will become a new therapeutic strategy for IIM. References: [1] Noack M, Miossec P. Th17 and regulatory T cell balance in autoimmune and inflammatory diseases.[J]. Autoimmunity reviews, 2014, 13(6):668–677. [2] Bluestone J A, Trotta E, Xu D. The therapeutic potential of regulatory T cells for the treatment of autoimmune disease.[J]. Expert opinion on therapeutic targets, 2015, 19(8):1091–1103. [3] Vercoulen Y, Bellutti Enders F, Meerding J, et al. Increased presence of FOXP3+ regulatory T cells in inflamed muscle of patients with active juvenile dermatomyositis compared to peripheral blood.[J]. PloS one, 2014, 9(8):e105353. [4] Young N A, Sharma R, Friedman A K, et al. Aberrant muscle antigen exposure in mice is sufficient to cause myositis in a Treg cell-deficient milieu.[J]. Arthritis and rheumatism, 2013, 65(12):3259–3270. [5] Milward K F, Wood K J, Hester J. Enhancing human regulatory T cells in vitro for cell therapy applications.[J]. Immunology letters, 2017, 190:139–147. Acknowledgements: Thanks for my teachers, classmates and my famliy. Disclosure of Interest: None declared